FACTORS INFLUENCING GOING CONCERN AUDIT OPINION AMONG BASIC MATERIALS COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) DURING THE PERIOD OF 2019-2021 - Kristian, Michelle; Tanusdjaja, Hendang; Catherine , Catherine; Siswanto, Halim Putera (International Journal of Application on Economics and Business, 2024)
The purpose of this research is to obtain empirical evidence about the effects of profitability, liquidity, solvency, and firm size on going concern audit opinion in basic materials companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This research uses firm age as control variable. This research uses 49 samples and 147 data from basic materials companies selected by the purposive sampling method. Data processing techniques uses logistic regression analysis and processed using SPSS version 26. The result of this research indicate that profitability has a negative and significant effect on going concern audit opinion, solvency has a positive and significant effect on going concern audit opinion, liquidity and firm size have no significant effect on going concern audit opinion.